Efeito da placa de Michigan sobre o sinal eletromiogr??fico e dor em pacientes bruxistas com DTM: ensaio cl??nico controlado e randomizado - Jesus, Luciane Anuncianto de (2008)
The aim of this study was to assess the prevalence of temporomandibular disorders (TMD) and bruxism among Brazilian college students and evaluate the effects of Michigan splint on pain and eletromyography behavior, before and after treatment. Were interviewed 832 students, from both sexes, in ages ranging from 19 to 40 years old using the Fonseca s Questionnaire of these, following the calculation of the sample to contemplate the second objective, 45 subjects were selected, divided in three groups with 15 individuals. The groups I and II were composed by subjects with TMD and bruxism signals and symptoms. The group I was treated with Michigan splint and group II with no therapeutically splint. The participants who had received treatment had made use of the plate per four weeks. The group III (control) do not received any type of treatment. The results showed that the 576 (69.23%) subjects presented some level of TMD and 256 (30.57%) do have no TMD. Among the TMD patients only 107 (18.57%) were bruxists. There was a significant correlation between the degree of TMD and bruxism (p<0,0001) showing a greater incidence of bruxism according to the increased of the TMD severity. However, was not observed significant differences on pain and electromyography activity of the evaluated muscles, during rest, isotonic and isometric contractions on pre and post treatment and in any group (p> 0,005). We concluded that had a high prevalence of DTM in Brazilian college s student and that a correlation exists between the TMD severity and bruxism. The treatment with Michigan splint during 4 weeks had not been enough to promote the pain relief and to modify the electric activity of the studied muscles.